mpact of Covid-19 Pandemic on Career Plans and Entrepreneurship Intentions of Students in Muhammadiyah Magelang University - Syaidah, Wulan Dewi Fatikhatus; Nisaa, Urmilla Fakhrun; Maharani, Jasmine Nabila; Setiadi, Namira Assyafira; Husna, Aftina Nurul (Prosiding University Research Colloquium, 2022)
This study aims to determine the effect of student entrepreneurship intentions on career plans due to the impact of the Covid-19 Pandemic. Entrepreneurial intention can be interpreted as a process of seeking information to achieve a business goal. According to data obtained from the central statistics agency, data on the increasing number of unemployed, from 2019 to 2020 increased by 1.84% so that the number of unemployed becomes 7.07%. In addition, the difficulty of finding a job is also one of the causes of someone becoming unemployed. The method used in this study is a quantitative method using a descriptive survey. The participants of this study were "Active" students at Muhammadiyah Magelang University. The data was taken by distributing google forms through the Administration (TU) of each Faculty at the University of Muhammadiyah Magelang. The technique used in this research is the snowball sampling technique which is carried out online. The number of participants obtained is N=78. Then the data was analyzed using the SPSS 26 program for windows or a newer version. The results of this study found that the frequency of entrepreneurial intentions of students at the University of Muhammadiyah Magelang was in the "MEDIUM" category. In conclusion, from the results of these calculations, it can be seen that the career plans of students at the University of Muhammadiyah Magelang to become entrepreneurs are still in the medium category.